Just sit still and pay attention? The importance of physical activity in schools - Neuendorf, Caitlyn (Kansas State University, 2019)
The majority of young people spend a large proportion of their time at school, yet many of them do not have adequate opportunities to obtain the recommended amount of moderate to vigorous physical activity (MVPA). The public health crisis associated with physical inactivity has an influence on children’s physical and mental health. Achieving adequate amounts of physical activity can raise students’ test scores and enhance their ability to focus. Given the benefits for health and well-being, it seems inconceivable that schools would contribute to depriving students of opportunities to be active by limiting physical education and withholding recess. If decision makers or policy makers use evidence to inform both policies and practices that promote and require physical activity opportunities in schools, then students will develop healthy habits that will ultimately reduce the prevalence of chronic disease, enhance academic success, and positively contribute to overall well-being.
Keywords: Children; School health; Wellness policy; Nutrition education; Health promotion; Academic achievement